A qualitative study of children’s quality of life in the context of living with cleft lip and palate - Zeraatkar M; Ajami S; Nadjmi N; Faghihi SA; Golkari A (Dove Medical Press, 2019)
Maryam Zeraatkar,1 Shabnam Ajami,2 Nasser Nadjmi,3 Seyad Aliakbar Faghihi,4 Ali Golkari1 1Oral and Dental Disease Research Center, Department of Dental Public Health, Shiraz University of Medical Sciences, Shiraz, Iran; 2Orthodontic Research Center, Department of Orthodontics, Shiraz University of Medical Sciences, Shiraz, Iran; 3Department of Cranio-Maxillofacial Surgery, Antwerp University Hospital, Antwerpen, Belgium; 4Clinical Educational Research Center, Shiraz University of Medical Sciences, Shiraz, Iran Background and objective: Quality-of-life measures have been expanded to help in assessing the physical and psychosocial effects of oral health. Although, in the case of children undergoing oral surgery, the oro-facial status is generally measured by studies, it is essential to carry out investigations into the level of quality of life (QoL) after surgery to assess the actual effect of these surgeries on children’s lives. Hence, our study is aimed at evaluating the QoL in these children. Methods: The study was performed using qualitative content analysis method. Eighteen caregivers of 4–6 year old children with a history of unilateral cleft lip and palate participated in in-depth interviews about the children’s experiences with different problems affecting their daily lives. The results were divided into codes, sub-categories and categories through an inductive process in which the researchers moved from the specific to the general. Result: A number of problems were identified, particularly insufficient functional and socio-emotional well-being including, difficulty in eating and speaking, dento-facial problems, shame, anxiety, insufficient peer interaction and dissatisfaction with their own appearance. Conclusion: The most critical problems derived from the participants’ experiences were insufficient functional and socio-emotional well-being that contributed to the reduced QoL among these children. Long term multidisciplinary interventional strategies such as psycho-social supportive programs are required to improve the QoL of these children. These interventions should be considered from the early stages of treatment, or even early stages of diagnosis. Keywords: children, cleft lip, cleft palate, quality of life